Konsep Pengetahuan Sejarah Ibnu Taimiyah Pada Masa Yunani Dan Islam - Hendra Hendra; Angga Pradana Kusuma (Universitas Dian Nuswantoro, 2022)
This study aims to analyze the concept of historical knowledge put forward by Ibn Taimiyah during the ancient Greek period and the development of Islam. Ibn Taimiyah is an Islamic scholar who lived in the 13th century AD, while ancient Greece is an important period in the history of human civilization which includes the classical and Hellenistic periods. The research method used is descriptive qualitative, by explaining more emphasis on the power of data analysis on existing data sources. The results showed that Ibn Taimiyah had a deep understanding of history and considered it an important source of knowledge. He stressed the importance of studying and understanding history as an effort to understand the journey of humanity and take lessons from the past. Ibn Taimiyah also highlighted the importance of understanding and criticizing existing historical sources in order to gain an accurate and objective understanding